Use of surveillance colonoscopy among individuals with removal of high‐risk polyps according to the US Multi‐Society Task Force recommendations. Issue 9 (17th February 2023) - Knudsen, Markus D.; Wang, Kai; Berstad, Paula; Polychronidis, Georgios; Vithayathil, Mathew; Song, Mingyang
Abstract: Background: Individuals with colorectal polypectomy are recommended to undergo surveillance colonoscopies at certain intervals to prevent subsequent colorectal cancer. Use of postpolypectomy surveillance according to the 2006 US Multi‐Society Task Force (USMSTF) recommendations in an integrated health care system was investigated. Methods: Use of surveillance colonoscopies was prospectively assessed among 3691 patients with removal of high‐risk polyps at a screening colonoscopy during 2007–2012 in the Mass General Brigham Colonoscopy Cohort. With the follow‐up up to 2017, the compliance with, overuse, and underuse of postpolypectomy surveillance according to the 2006 USMSTF recommendations was assessed. Surveillance use according to demographic factors was also investigated. Results: During a median follow‐up of 4.4 years (5th percentile, 95th percentile, 1.0, 9.9) 2360 (64%) patients had undergone a surveillance colonoscopy, among whom 758 (21%) were considered compliant with the USMSTF recommendations. A substantial underuse of surveillance colonoscopies of 62% was observed. Older age and lower income were associated with a higher incidence of underuse, whereas having a family history of colorectal cancer were associated with lower incidence of underuse. Overuse of surveillance colonoscopies was present in 17% of patients but showed no significant associations with demographic factors. Conclusion: Substantial underuse of surveillance in patients with high‐risk polyps was observed, particularly those with low income and older age. Efforts are needed to improve delivery and use of surveillance colonoscopy. Plain Language Summary: The US Multi‐Society Task Force recommends follow‐up surveillance colonoscopy after polyp removal in the bowel, with intervals depending on the most severe findings. Adherence to surveillance recommendations in a large study with up to 10 years of follow‐up among patients with high‐risk polyps was investigated. Only 21% of patients adhered to the surveillance recommendations, whereas 62% showed delayed or no use of surveillance. Findings highlight the need for improved use of surveillance colonoscopy among patients at high risk of colorectal cancer. Abstract : There was substantial noncompliance with the US Multi‐Society Task Force recommendations for surveillance colonoscopy among patients with high‐risk polyps. These findings highlight the need to improve the use of surveillance colonoscopies after polypectomy.